Use of Laser Systems in Orthodontics - Kevser Kurt Demirsoy; Gökmen Kurt (Galenos Yayinevi, 2020)
Laser systems have been used in the practice of dentistry for >35 years. Laser systems have so many advantages, such as increase patient cooperation, reduce the duration of treatment time, and help the orthodontists to enhance the design of a patient's smile to improve treatment efficacy, and the success of orthodontic treatments can also be improved by diminishing the orthodontic pain and the discomfort of the patients. Laser systems also have some disadvantages, such as cost, large space requirements for some types, and high-risk potential for physician and patient if not used at the appropriate wavelength and power density, that is why before incorporating lasers into clinical practice, the physician must fully understand the basic science, safety protocol, and risks associated with them. Lasers have many applications in orthodontics, including accelerating tooth movement, bonding and debonding processes, pain reduction, bone regeneration, etching procedures, increase mini-implant stability, soft tissue procedures (gingivectomy, frenectomy, operculectomy, papilla flattening, uncovering temporary anchorage devices, ablation of aphthous ulcerations, and exposure of impacted teeth), fiberotomy, scanning systems, and welding procedures. In reviewing the literature on the use of laser in orthodontics, many studies have been conducted. The purpose of the present study was to give information about the use of laser in the field of orthodontics, the effects of laser during the postoperative period, and its advantages and disadvantages and to provide general information about the requirements to be considered during the use of laser.